Kajian Literatur Penerapan Model Problem Based Learning dalam Meningkatkan Pemahaman Konsep IPS pada Siswa Sekolah Dasar - Fatonah, Gina Siti Nurkarimah; Varianeta, Kalysa Marina; Wahyuningsih, Yona (Edu Berkah Khatulistiwa, 2026)
This study aims to examine the relationship between the application of the Problem Based Learning (PBL) model and the improvement of understanding of Social Studies (IPS) concepts in elementary school students through a literature study. The research method used is a literature study by reviewing various scientific sources such as journals, books, and relevant and credible research reports. Data were analyzed using descriptive analysis techniques to identify patterns of findings, advantages, and challenges in the application of PBL in social studies learning. The results of the study indicate that PBL is consistently related to an increase in understanding of social studies concepts, because students are directly involved in an authentic problem-solving process, thus being able to connect social concepts with real situations in their environment. PBL has also been shown to increase learning participation, curiosity, critical thinking skills, and higher-order thinking skills (HOTS). In addition, interaction and collaboration in groups make students more skilled in communicating ideas and developing solutions to social problems. However, the implementation of PBL faces several challenges such as the need for longer time, teacher readiness in designing contextual problems, and limited supporting learning resources. Overall, this study confirms that PBL is an effective, meaningful, and relevant learning strategy to improve the quality of social studies learning while supporting the development of 21st-century competencies in elementary school students.